Novel germline variant of TMEM127 gene in a patient with familial pheochromocytoma. (6th April 2017) - Saitoh, Kohei; Yonemoto, Takako; Usui, Takeshi; Takekoshi, Kazuhiro; Suzuki, Makoto; Nakashima, Yoshiharu; Yoshimura, Koji; Kosugi, Rieko; Ogawa, Tatsuo; Inoue, Tatsuhide
Summary: Pheochromocytomas (PCCs) and paragangliomas (PGLs) are rare tumours with a heterogeneous genetic background. Up to 40% of apparently sporadic PCC/PGL cases carry 1 of the 12 gene germline mutations conferring genetic susceptibility to PCC/PGL. Although the precise mechanisms are unclear, TMEM127 is one of the rare responsible genes for PCC/PGL. Here we report the case of a patient with familial PCC having a novel TMEM127 variant (c.119C > T, p.S40F). In silico prediction analysis to evaluate the functional significance of this variant suggested that it is a disease-causing variant. A PCC on the left side was considered to be the dominant lesion, and unilateral adrenalectomy was performed. The histopathologic findings were consistent with benign PCC. A loss of heterogeneity of the TMEM127 variant was detected in the surgically removed tumour. Learning points: c.119C > T (p.S40F) is a novel TMEM127 variant that can cause pheochromocytoma. The tumour showed loss of heterozygosity of this TMEM127 variant. The clinical phenotype of this mutation is putative bilateral pheochromocytoma in the 4th decade. Unilateral adrenalectomy may be performed as the initial surgery in such cases.